2019
DOI: 10.1108/bfj-07-2019-0553
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin as substitute for texture ingredients in ice creams

Abstract: Purpose The phycocyanin is a pigment present in the microalga Spirulina that has been studied due to its applicability as food coloring; however, it can be used due to the ability to act as an emulsifier or stabilizer in function of its protein characteristic. The purpose of this paper is to use aqueous extracts of Spirulina containing phycocyanin (EP) as a substitute of additives in the production of ice creams. Design/methodology/approach The study was divided in two sections: first, the influence of addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, when microalgae derivatives such as pigments are incorporated, a different behavior can be observed in the melting time of ice cream. Rodrigues et al [ 80 ] reported that the use of 0.5% w / v phycocyanin as a substitute for stabilizers in ice cream resulted in shorter relative first drop times (below 10.0 s.g −1 ) when compared to the control (13.0 s.g −1 ), which indicates that this pigment does not improve the stabilizing capacity of the ice cream.…”
Section: Applications Of Microalgal Biomass and Its Derivatives In Ic...mentioning
confidence: 99%
“…On the other hand, when microalgae derivatives such as pigments are incorporated, a different behavior can be observed in the melting time of ice cream. Rodrigues et al [ 80 ] reported that the use of 0.5% w / v phycocyanin as a substitute for stabilizers in ice cream resulted in shorter relative first drop times (below 10.0 s.g −1 ) when compared to the control (13.0 s.g −1 ), which indicates that this pigment does not improve the stabilizing capacity of the ice cream.…”
Section: Applications Of Microalgal Biomass and Its Derivatives In Ic...mentioning
confidence: 99%
“…The replacement of stabilizers and emulsifiers with phycocyanin extract did not change sensorially the overall acceptability of the product. Rodrigues et al (2020) Ice cream Spirulina platensis LEB-52 C-phycocyanin, a protein with bioactive properties, was extracted from Spirulina dry biomass, purified, and applied in an ice cream formulation. The product showed a blue color that remained stable over six months.…”
Section: Spirulina : Functional Foods and Emerging Technologiesmentioning
confidence: 99%
“…Microalgae represent a non-animal source of protein and have higher contents compared to beef, pork, and dairy products, also to superior amino acid quality ( de Medeiros et al, 2021 ). Microalgae biomass can also contribute to adding bioactive compounds to the food, for example, carotenoids ( Lucas, de Morais, Santos, & Costa, 2018 ), phenolic compounds ( de Oliveira et al, 2021 ), and the blue pigment found in Spirulina, phycocyanin, which in addition to contributing to the color, is also characterized by its antioxidant potential ( de Amarante et al, 2020 , Faresin, Devos, Reinehr, & Colla, 2022 ; Rodrigues et al, 2020 ). With the addition of Spirulina in food formulations, authors also found an increase in the concentration of minerals ( Almeida et al, 2021 , Carvalho et al, 2017 , Lucas et al, 2018 ).…”
Section: Spirulina : Functional Foods and Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirulina platensis biomass was supplied provided by the Federal University of Rio Grande, with the following chemical composition in dry basis: 71.8% crude protein, 11.2% carbohydrates, 2.9% lipids and 14.1% ash. The percent of total solids of dry biomass was 90% [17]. Aspergillus niger, isolated in a previous work [18] was used for solid state fermentation.…”
Section: Raw Materials and Microorganismsmentioning
confidence: 99%